2010
DOI: 10.1002/anie.201001884
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Rheb and K‐Ras4B GTPases

Abstract: Now available! Farnesylated and carboxymethylated Rheb (see picture) and K‐Ras4B GTPases were synthesized in useful amounts by a combination of expressed protein ligation and solid‐phase lipopeptide synthesis. The functionality of the proteins was proven by biochemical, biophysical, and cell‐based investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 44 publications
4
87
0
2
Order By: Relevance
“…In contrast, the affinity between PDE6δ and the farnesylated C-terminal peptide of Rheb falls into the submicromolar range ( K d =445±83 nM,±indicates s.d., n =10) (Fig. 1b; right), which is in the same range with the previously described values1213. These data raised the question, whether the almost 100-fold higher affinity of INPP5E towards PDE6δ as compared to Rheb is involved in the sorting mechanism of these two proteins to different destinations.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In contrast, the affinity between PDE6δ and the farnesylated C-terminal peptide of Rheb falls into the submicromolar range ( K d =445±83 nM,±indicates s.d., n =10) (Fig. 1b; right), which is in the same range with the previously described values1213. These data raised the question, whether the almost 100-fold higher affinity of INPP5E towards PDE6δ as compared to Rheb is involved in the sorting mechanism of these two proteins to different destinations.…”
Section: Resultssupporting
confidence: 85%
“…Given that the prenyl-binding protein PDE6δ is the shuttle factor mediating the localization of INPP5E and Rheb1316182526, we set out to characterize the interaction of PDE6δ with INPP5E and Rheb. Previously we have shown that farnesylated C-terminal peptides derived from Rheb or KRas bind to PDE6δ in exactly the same way and with similar affinities as the full-length farnesylated proteins1213. Hence, we used a fluorescently labelled C-terminal farnesylated and carboxy-methylated peptide of INPP5E (residues 637–644) and Rheb (residues 175–181) to measure the affinity to PDE6δ by fluorescence polarization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results show that the presence of both the methyl and farnesyl modifications increases the affinity between KRAS4b and PDEδ close to two orders of magnitude compared with only KRAS4b-Far. Previous studies using a fluorescence-polarization (FP) assay showed a 10-fold higher binding affinity (K d = 0.3 μM) between KRAS4b and PDEδ (29). This discrepancy is likely caused by the use of different techniques (analytical ultracentrifugation and ITC vs. FP), different assay conditions, and the use of semisynthetic and refolded KRAS4b vs. recombinant fully processed KRAS4b that we used for this study.…”
Section: The Role Of Farnesyl and Methyl Groups In Interactions Betweenmentioning
confidence: 82%
“…GSF=GDI solubilising factor, NA=not available and text in red indicates that the prediction has not been verified experimentally yet. References are [8,9,22,38,43,44].…”
Section: Open Questions and Future Perspectivesmentioning
confidence: 99%